The effect of environmental, social, and governance practices on profitability performance with financial slack as a moderator - Kautsar Riza Salman; Herwin Ardianto; Entis Sutisna; Jana Siti Nor Khasanah (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2024)
This study aims to obtain empirical evidence on the effects of environmental, social, and governance (ESG) on the profitability performance of Islamic companies, incorporating the moderating effect of financial slack in this relationship. The sample includes Islamic companies listed on the Jakarta Islamic Index 70 (JII 70) and the SRI KEHATI index over the 2021-2023 period, resulting in 129 firm-year observations. Panel data analysis using Eviews 13 software identified the Random Effect Model as the best approach. Findings indicate that ESG practices significantly affect profitability, supporting agency theory by suggesting that management may engage in ESG activities that incur costs without clear financial benefits for shareholders. Financial slack does not moderate the ESG-profitability relationship. Instead, financial slack, proxied by the cash ratio, directly impacts profitability. These findings suggest that while ESG practices may have profitability trade-offs, financial flexibility could enhance profit potential in Islamic companies. For policymakers, these results underscore the need to tailor ESG frameworks to the unique financial dynamics of Islamic companies, potentially aiding these firms in achieving both sustainable and profitable growth.